1990
DOI: 10.1007/bf01833322
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and strontium activation characteristics of skeletal muscle fibres from the small marsupialSminthopsis macroura

Abstract: Mechanically skinned skeletal muscle fibres from the soleus and tibialis anterior muscles of the small marsupial Sminthopsis macroura were activated by Ca2+ and Sr2+ so that their isometric force properties could be determined. The properties characterized were the shape, slope and positions of the curves generated by plotting isometric force vs. pCa (-log10[Ca2+]) and pSr (-log10[Sr2+]), the maximum Ca2(+)-activated and Sr2(+)-activated tension (Ncm-2) and the frequency of force oscillations of myofibrillar o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…4A. The curve fitted through the data points from the fresh fibre was similar to a classical sigmoidal Hill curve Fink et al 1986;Wilson & Stephenson, 1990) generated using an n value of 8-0 and showed that the mid-point for force activation (pCa50) was 5-84. After DTNB treatment for 10 s Pr fell to 14% of P0.…”
Section: Fibre Stiffnessmentioning
confidence: 61%
See 2 more Smart Citations
“…4A. The curve fitted through the data points from the fresh fibre was similar to a classical sigmoidal Hill curve Fink et al 1986;Wilson & Stephenson, 1990) generated using an n value of 8-0 and showed that the mid-point for force activation (pCa50) was 5-84. After DTNB treatment for 10 s Pr fell to 14% of P0.…”
Section: Fibre Stiffnessmentioning
confidence: 61%
“…Fast-twitch and slow-twitch fibres were classified according to their Ca2+-activation characteristics at different pCa (pCa = -loglo[Ca2"]) levels and according to whether they possessed low-frequency force oscillations of myofibrillar origin when submaximally Ca2"-activated (Stephenson & Williams, 1981;Fink et al 1986;Wilson & Stephenson. 1990).…”
Section: Skinned Fibresmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of the effects of Ca2+ and Sr2+ activation was achieved by construction of force-pCa and force-pSr curves for the contractile responses of each individual skinned fibre as previously described in detail (Fink et al 1990;Wilson & Stephenson, 1990;Lynch et al 1991 The procedure for classifying fibres into respective types. on the basis of' their contractile characteristics has been described in detail previously (Wilson & Stephenson 1990.…”
Section: Discussionmentioning
confidence: 99%
“…on the basis of' their contractile characteristics has been described in detail previously (Wilson & Stephenson 1990. Individual fibres were only allocated to one of the two major fibre-type groups.…”
Section: Discussionmentioning
confidence: 99%